2017
DOI: 10.1371/journal.pone.0182357
|View full text |Cite
|
Sign up to set email alerts
|

The molecular mechanism of the anticancer effect of Artonin E in MDA-MB 231 triple negative breast cancer cells

Abstract: Nature has provided us with a wide spectrum of disease healing phytochemicals like Artonin E, obtained from the root bark of Artocarpus elasticus. This molecule had been predicted to be drug-like, possessing unique medicinal properties. Despite strides made in chemotherapy, prognosis of the heterogenous aggressive triple negative breast cancer is still poor. This study was conducted to investigate the mechanism of inhibition of Artonin E, a prenylated flavonoid on MDA-MB 231 triple negative breast cancer cell,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 59 publications
3
24
0
1
Order By: Relevance
“…In general, these results are in good agreement with the findings already documented in the scientific literature that SKBR3 is a HER2-overexpressing cell line [ 33 ], MCF-7 and T47D are low HER2-overexpressing cell lines [ 34 ] and MDA-MB-231 is considered triple negative (no expression of HER2, progesterone and estrogen receptors) [ 35 ]. Russo et al reported that HER2 expressed at T47D is predominantly cytosolic [ 36 ].…”
Section: Resultssupporting
confidence: 90%
“…In general, these results are in good agreement with the findings already documented in the scientific literature that SKBR3 is a HER2-overexpressing cell line [ 33 ], MCF-7 and T47D are low HER2-overexpressing cell lines [ 34 ] and MDA-MB-231 is considered triple negative (no expression of HER2, progesterone and estrogen receptors) [ 35 ]. Russo et al reported that HER2 expressed at T47D is predominantly cytosolic [ 36 ].…”
Section: Resultssupporting
confidence: 90%
“…1. This study is designed to investigate the cell killing efficacy of PDT using our actively targeted nanoformulation (PLGA-PEG hTf BPD, referred to as "ANP") and compare it to both BPD in its free form (referred to as "free BPD") and passively targeted (PLGA-PEG BPD or "PNP") nanoparticles on TNBC cell line MDA-MB-231 (34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…Together, these findings indicate that BIRC7 promoted the progression and metastasis of breast cancer through the regulation of EMT by activating the p38/GSK3β pathway. A deeper understanding of the role of BIRC7-induced EMT in breast cancer may provide effective targets for therapy, especially in triple-negative breast cancer (Han et al, 2017, Etti et al, 2017).…”
Section: Breast Cancermentioning
confidence: 99%